Chemotherapy effectiveness and age-group analysis of older adult patients with metastatic pancreatic cancer: A Japanese cancer registry cohort study. Issue 8 (November 2022) - Daiku, Kazuma; Ikezawa, Kenji; Morishima, Toshitaka; Kai, Yugo; Takada, Ryoji; Yamai, Takuo; Miyashiro, Isao; Ohkawa, Kazuyoshi
Abstract: Introduction: Although older adults aged ≥75 years comprise a substantial proportion of patients diagnosed with pancreatic cancer (PC), the effectiveness of chemotherapy in older adults with PC remains to be established. Materials and Methods: This retrospective study examined the effectiveness of chemotherapy according to age in older adult patients with metastatic PC. We used a large database that combined three data sources (the hospital-based cancer registry database, Osaka Cancer Registry, and Japan's Diagnosis Procedure Combination) and extracted data from patients pathologically diagnosed with metastatic PC between 2013 and 2015 in 31 designated cancer care hospitals in Japan. Propensity score matching (PSM) was used to identify a cohort of patients with similar backgrounds. The effect of chemotherapy on overall survival (OS) was analyzed using the log-rank test. Results: Compared with 687 younger patients (<75 years old), 276 older adult patients had significant impairments in activities of daily living and poorer prognoses (6.8 vs. 4.1 months, p < 0.001), with a lower frequency of chemotherapy (81.5% vs. 55.1%; p < 0.001). PSM of older adult patients showed that chemotherapy significantly contributed to a better prognosis (best supportive care, 2.6 months vs. chemotherapy, 5.8 months, p < 0.001). Age group analysis with PSM of five-year age ranges revealed that the median OS was significantly longer in the chemotherapy group among older adult patients aged <85 years. Discussion: Chemotherapy provides a survival benefit in older adult patients with metastatic PC, and patients aged <85 years could be promising candidates for chemotherapy.